Canon EOS Rebel T4i/650D digital field guide - Sillars, Rosh, 1968- (Digital field guide., 2013)
BMaster every detail of this exciting new touchscreen dSLR/b Canon's new introductory-level dSLR camera boasts some revolutionary features that will be new even to Canon veterans. This convenient guide effectively explains every button, menu, mode, and function of the Rebel T4i/650D, and it fits in your camera bag so you can easily refresh your memory during a shoot. With step-by-step descriptions of every action and feature plus color images of every control, this little book will have you taking charge of your camera in no time. Learn to use the touchscreen menus, new silent autofocus feature, and extended ISO range. You'll also get suggestions for improving your shots in specific situations. There's even a free gray and color checker card to help you achieve perfect color and white balance every time.ulliThe Canon EOS Rebel T4i/650D offers a touchscreen, silent autofocus mode for better quality video shooting, and a broader ISO range for improved photo quality in low-light conditionsliThis handy guide clearly explains every feature, mode, dial, function, and menu, illustrating the instructions with plenty of full-color imagesliExplains how and when to use various features and provides great advice on a number of common shooting situationsliConvenient 6x9-inch trim size makes it easy to take the book along for reference, and the bonus gray and color checker card inside helps assure you of accurate color /ul iCanon EOS Rebel T4i/650D Digital Field Guide/i is the perfect partner to help you get the most from your exciting new Canon dSLR.